Inovasi Cascara Berbasis Pemberdayaan Masyarakat di Desa Kutambaru - Faris, Salman; Anggraini, Sari; Saprida, Saprida (Universitas Medan Area, 2026)
This Community Service Program (PKM) aims to empower coffee farmers in Kutambaru Village, Munte District, Karo Regency, by valorizing coffee husk waste into economically valuable cascara products. The problems faced by the partners include the underutilization of coffee waste, limited knowledge of product diversification, and inadequate managerial and marketing capacities. The program was implemented using a participatory approach through socialization, cascara production training, basic business management training, and digital marketing assistance. The evaluation results indicate an improvement in participants’ capacity. At the initial stage, 60% of participants had no prior knowledge of coffee husk valorization and cascara products. After the program, 100% understood the processing stages, and 70% were able to independently practice production. In addition, around 60% of participants demonstrated initial understanding of agroindustry management and digital marketing. The program produced pure and spiced cascara products, along with outputs including a simple business plan, product branding, and digital marketing accounts to support the development of a sustainable community-based agroindustry.